A quantitative overview of dentinal hypersensitivity in the private practice patient population of north India: A short study - Goel, Roshni; Agarwal, Sanjay; Kumar, Prince; Kumar, Ashish; Singh, Harkanwal P.; Khattar, Ashish (European Journal of General Dentistry, 2012)
Dentine hypersensitivity (DH) is a well known and one of the most widely investigated clinical entity; still, studies based on randomly selected general practice populations are very less. The present study was designed to scrutinize the intraoral distribution of DH and its relationship with age, sex, symptoms, stimuli, predisposing factors and management strategies in the North Indian private practice patient population. The study was designed as a short survey based on questionnaire and was conducted on the randomly selected North Indian private dental practice dentists. It was concluded that dietary acid, gingival recession and erosion were potentially associated with DH, with a strong predilection for middle-aged females.
Keywords: Dentine hypersensitivity; erosion; survey